Pengaruh Kualitas Interaksi, Teknologi Pendukung, dan Ciptaan Kenangan terhadap Indeks Kepuasan Wisatawan Bali Zoo - Prasetya Dewi, Made Indah; Juwita Sari, Putu Ratna; Sedana Putra P, Komang Widhya; Paramitha Pika, Putu Ayu Titha (Masyarakat Ekonomi Syariah Bogor, 2025)
This study aims to determine the partial and simultaneous influence of service quality, digitalization, and travel experience on tourist satisfaction. The sample in this study was 152 domestic tourists, aged at least 17, who had visited Bali Zoo and used social media. Data analysis techniques used Validity Test, Reliability Test, Classical Assumption Test, Multiple Linear Regression Analysis, Coefficient of Determination Test, F-Test, and t-Test. The results showed that service quality had a positive and significant effect on tourist satisfaction, digitalization had a positive and significant effect on tourist satisfaction, and travel experience had a positive and significant effect on tourist satisfaction. The researcher recommends that Bali Zoo management improve employee capabilities in providing fast and responsive service by providing training focused on providing service-related materials, continuously updating digital information and providing honest and accurate information, making improvements to areas lacking attractive visual displays, and striving to continuously provide good service and a memorable travel experience for tourists, to enhance tourist satisfaction.